Genotoxicity Studies in Groundwater, Surface Waters, and Contaminated Soil - Luc Verschaeve (The Scientific World Journal)
It is at present considered important to include biological tests in measuring programmes of environmental samples to supplement the chemical and physical parameters that are currently used. A battery of tests is therefore necessary, also within a given “endpoint” (e.g., genotoxicity), because one single test will not give all the answers to our questions. As it is not possible to include all available tests in routine screening programmes, a selection of tests should be made. According to comparative investigations, the bacterial Ames test remains very important. When no preconcentration step is involved, other bacterial tests (e.g., the umu-C and VITOTOX® tests) may be recommended. The comet assay may be used in Daphnia or human white blood cells. Further validations, comparisons, mechanistic investigations, etc. remain necessary as differences are often found between the tests that are not solely explained by differences in genetic endpoint and that therefore should further be investigated and understood.